Tatalaksana Penyakit Glositis Atrofi akibat Defisiensi Zat Besi dan Vitamin B12 - Naoval Afif, Muhammad Yusril (Faculty of Medicine, Universitas Mataram, 2023)
Introduction : Atrophic glossitis is a disease of the tongue that causes inflammation or inflammation, then gives the appearance of a red tongue color with a smooth dorsum accompanied by pain and burning. Atrophic glossitis occurs when the fungiform and filiform papillae on the dorsum of the tongue are lost by as much as 50%. This is due to sufferers who have nutritional deficiencies, such as deficiency of B12, iron, folic acid, riboflavin, and niacin. This article aims to determine the general and specific management of atrophic glossitis. Method : The writing of this article includes various sources originating from scientific journals and government guidelines and related agencies. Source searches were conducted on online journal publication portals such as MedScape, Google Scholar (scholar.google.com) and the National Center for Biotechnology Information (ncbi.nlm.nih.gov), with the keyword